The use of hand-reared ducks for supplementing wild populations - Boyd, Hugh (Wildfowl, 1956)
Hand-rearing of ducks for shooting has long been practised in Britain. Until recently such rearing was undertaken only by landowners, or their tenants, for their own immediate benefit. In the last two years the Wildfowler's Association of Great Britain and Ireland has been advocating the rearing of ducks for release in the wild by its members, individually or collectively, and some of its local organisations put such schemes into practise in 1955. The novelty and interest of these schemes lies in the fact that few of the members of W.A.G.B.I. are landowners, and the majority are probably only able to indulge in fowling on the foreshore. Two lines of inquiry suggest themselves. First, will duck-rearing schemes improve the sport of members of W.A.G.B.I.? Second, will such schemes in due course do much to increase our wildfowl populations as the Annual Report of their Association for 1953-54 suggests? The two questions are related, though by no means identical. This discussion of them is based on a number of papers published in America in the last 20 years dealing with similar problems, analyses by the writer of the results of British Mallard ringing (see Boyd 1954, but largely unpublished), and various observations on the behaviour of ducks and wildfowlers.